2011
DOI: 10.1038/ijo.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weight bias following weight loss: the impact of weight-loss method

Abstract: Background: Many obese individuals lose weight to reduce weight stigma; however, little is known about whether other people's attitudes actually improve towards obese individuals after they have lost weight, and whether changes in attitudes depend on the method of weight loss. This study examined changes in people's perceptions of an obese target who had lost weight through diet and exercise or through surgery. Method: Participants (N ¼ 73) initially viewed an image of an obese woman or a thin woman (control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
3
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 23 publications
7
39
3
15
Order By: Relevance
“…Our results are only partly consistent with this hypothesis: We found that evaluations were most positive for the obese target who put in effort despite having uncontrollable body weight (i.e., the weight-uncontrollable high-effort target). Recent research indicates that individuals who lose weight through effort (diet and exercise) are viewed more favorably than are individuals who lose weight through surgery (Fardouly & Vartanian, 2012;Mattingly et al, 2009;Vartanian & Fardouly, 2013. The present findings extend this literature by demonstrating that people who put in effort can be viewed more favorably even if weight loss has not occurred and the individual is still obese.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results are only partly consistent with this hypothesis: We found that evaluations were most positive for the obese target who put in effort despite having uncontrollable body weight (i.e., the weight-uncontrollable high-effort target). Recent research indicates that individuals who lose weight through effort (diet and exercise) are viewed more favorably than are individuals who lose weight through surgery (Fardouly & Vartanian, 2012;Mattingly et al, 2009;Vartanian & Fardouly, 2013. The present findings extend this literature by demonstrating that people who put in effort can be viewed more favorably even if weight loss has not occurred and the individual is still obese.…”
Section: Discussionsupporting
confidence: 71%
“…For example, previously overweight or obese individuals who had lost weight through diet and exercise (high effort) were perceived more positively than were targets who had lost weight via surgery (low effort) (Fardouly & Vartanian, 2012;Mattingly, Stambush, & Hill, 2009;Vartanian & Fardouly, 2013, and this difference appears to be due to people viewing surgery patients as less responsible for their weight loss (Vartanian & Fardouly, 2013. Furthermore, Bullock, Stambush, and Mattingly (2011) showed that the difference between positive evaluations of high-effort targets relative to low-effort targets was most evident among individuals who were high in anti-fat attitudes.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…These findings seem to be particularly relevant as weight loss is hard to maintain (e.g., Dansinger, Tatsioni, Wong, Chung, & Balk, 2007;Wadden, Butryn, & Byrne, 2004) and may not necessarily diminish weight-related stigma (Fardouly & Vartanian, 2012;Latner, Ebneter, & O'Brien, 2012). Thus, recently researchers have been highlighting the importance of shifting the way individuals cope with their weight and weight-related experiences (including weight stigma) in order to increase their health-related quality-of-life (e.g., Blaine, Rodman, & Newman, 2007;Durso, Latner, White, et al, 2012;Hilbert, et al, 2013;Latner, et al, 2014;Lillis et al, 2010;Puhl & Bronwell, 2001;Puhl & Heuer, 2009;Tylka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…특히 미국에서는 이러한 편견을 줄이기 위해 병원이나 직장 및 학교에서 다양한 교육을 실시하고 있으며 보다 적극적 인 관리의 필요성을 보고하고 있다 (Kim et al, 2010). 최근 조 사에 따르면 비만도에 따라 승진, 고용선택 배치, 해임 등에서 심한 편견을 당한 것으로 나타났으며, 사회 ․ 심리적 스트레스, 신체 이미지 장애, 체중에 대한 사회적 압박으로 이어질 위험성 이 있다 (Fardouly & Vartanian, 2012;Kim et al, 2010) …”
unclassified